Performance analysis of elite female amateur boxers and comparison with their male counterparts - Davis, P.; Benson, P. R.; Waldock, R.; Connorton, A. J. (International Journal of Sports Physiology and Performance, 2016)
Female boxing debuted at the 2012 London Olympic Games. To better understand the performance aspects of the sport, video footage of eighteen 4 × 2-min bouts were analyzed. The boxers involved in the competition were of an elite level (mean ± SD), age 26.4 ± 4.6 y, height 169.3 ± 6.2 cm, and weight 60.3 ± 10.0 kg. Analysis revealed an activity rate of ~1.6 actions/s, including ~16 punches, ~3.3 defensive movements, and ~63 vertical hip movements, all per minute, over the 4 × ~132-s rounds (R). A 2 × 4 (outcome × round) ANOVA with repeated measures over the rounds was used to analyze the data. Winners maintained a higher activity rate in round 1 (R1) and R2; a higher movement rate in R2, R3, and R4; and an increased punch accuracy including the ratio of total punches to punches landed in R3 and air punches as a percentage of punches missed in R1 and R3. Specific techniques that discriminate between successful and unsuccessful female amateur boxers include the straight rear-hand and body punches, higher for winners in R1, as well as uppercut punches and defensive foot movements, higher for winners in R4. Findings highlight the current demands of elite amateur female boxing. These data will be useful for those designing training programs and may also be useful for guiding sport-specific fitness testing.